EXTH-64. COMPARISON OF PANOBINOSTAT CSF PENETRATION WITH CNS PENETRATION FOLLOWING SYSTEMIC ADMINISTRATION IN A PRE-CLINICAL NON-HUMAN PRIMATE MODEL. (12th November 2021) - McCully, Cynthia Lester; Warren, Katherine; Zimmerman, Sara; Peer, Cody; Rafael, Cruz Garcia; Kramer, Joshua; Breed, Matthew; Figg, William Douglas; Agar, Nathalie; Widemann, Brigitte
Abstract: Targeted therapies developed for diffuse midline gliomas (DMG) expressing H3K27M have focused on histone deacetylase inhibitors (HDACi). High-throughput drug screening with patient derived DMG cell lines identified the HDACi panobinostat as a prominent clinical agent as well as pre-clinical studies with orthotopic mouse tumors models proving efficacious. Diametrically there is a pronounced lack of measurable panobinostat CSF concentrations in a non-human primate (NHP) non-tumor bearing pre-clinical model and in pediatric brain tumor patients. Notwithstanding, adult and pediatric glioma clinical trials and clinical observation with panobinostat alone or in combination have demonstrated minor responses. Pharmacokinetic models utilize the premise that CSF drug penetration is a surrogate of CNS drug penetration. However, the direct correlation between CSF and CNS drug levels is undefined especially in lieu of geographic CNS extracellular fluid drug variability previously demonstrated in the same NHP pre-clinical model. Utilizing the same NHP model, this study sought to compare panobinostat CSF penetration to CNS penetration via analysis of homogenized normal cerebrum, cerebellum, and brainstem tissue utilizing LC-MS/MS. METHODS: Panobinostat was administered orally as a single dose to three non-human primates. Pre panobinostat plasma and CSF were collected. Following panobinostat administration (1-hr Tmax ) CSF, cerebrum, cerebellum, and brain stem tissue were collected as well as plasma to confirm the presence of panobinostat. Tissue slices were individually homogenized and panobinostat extracted via protein precipitation. Plasma, CSF, and tissue panobinostat concentrations were quantified using a LC-MS/MS assay. The lower limit of quantitation (LLOQ) for plasma-0.1 ng/ml, CSF-0.5 ng/ml, and tissue-10.0 pg/mg. RESULTS: Panobinostat was quantifiable in plasma (n=2) at the 1 hour (20.033 ng/mL and 0.153 ng/mL). CSF and CNS tissue samples were below the LLOQ for panobinostat in all samples. CONCLUSIONS: Panobinostat was not measurable from CSF and homogenized brain tissue in a non-tumor bearing NHP model at 1-hour post-administration using LC-MS/MS.